ANALISIS TINGKAT KEPUASAN PENGGUNA APLIKASI E-WALLET DANA MENGGUNAKAN METODE SUS - Nurul Huda; Daniel Adriano Tambunan; Femas Satria; Muhammad Rizki Bintang Putra (STORAGE: Jurnal Ilmiah Teknik dan Ilmu Komputer, 2023)
DANA application is a digital wallet platform designed to make transaction possible in a non-cash manner, whether online or offline. This study was used to determine the lvl of UI/UX usability in the DANA application using the System Usability Scale Method. The results in the DANA application obtained an average score of 72,41 with grade â€œBâ€ which stated that the DANA application was in the â€œExcelletâ€ category, and had acceptable ranges in the â€œHighâ€ category, which was caused by the small number of responses to odd questions on the questionnaire stating the application DANA is easy to use, while the even questions on the questionnaire state that the DANA application is difficult to use. So that the DANA application needs to improve the function of using the DANA application and make the application display easier to understand.